2000
DOI: 10.1063/1.372191
|View full text |Cite
|
Sign up to set email alerts
|

Colossal magnetoresistance in ultrathin epitaxial La0.75Sr0.25MnO3 films

Abstract: We present results on magnetotransport measurements of a series of La0.75Sr0.25MnO3 films with thickness ranging from 32 to 3300 Å. Films were fabricated using pulsed laser deposition onto SrTiO3 and LaAlO3 substrates. The substrate-film lattice mismatch causes strain in ultrathin films which diminishes with increasing thickness. Ultrathin films exhibit perfect match of in-plane film and substrate lattice parameters. The inhomogeneity of lattice parameters in thick films is caused by film-substrate mismatch st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 7 publications
1
31
0
2
Order By: Relevance
“…Compressive strain usually reduces the resistivity and shifts T C towards higher temperature. These effects have been confirmed in La 0.7 Ca 0.3 MnO 3 films 6,7 and La 0.7 Sr 0.3 MnO 3 films [8][9][10][11][12] grown on various substrates.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Compressive strain usually reduces the resistivity and shifts T C towards higher temperature. These effects have been confirmed in La 0.7 Ca 0.3 MnO 3 films 6,7 and La 0.7 Sr 0.3 MnO 3 films [8][9][10][11][12] grown on various substrates.…”
Section: Introductionmentioning
confidence: 68%
“…In epitaxial films, biaxial strain has been reported to have very strong effect on the changes in T C and insulator-metal transition temperature (T IM ) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Several publications have reported that both T C and T IM can vary with film thickness [14][15][16][17][18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…In epitaxial thin films grown on perovskite substrates, the biaxial strain that can be induced by lattice mismatch with the underlying substrate, film thickness, oxygen content, etc., provides an additional degree of freedom and, hence, influences the magnetic and transport properties. [11][12][13][14][15][16][17] In the case of a film grown on a given substrate, the strain mainly depends on the thickness. Beyond a critical film thickness, the strain is gradually relaxed and this aspect also has decisive influence on magnetic and transport properties, such as magnetization, T C , and T IM .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, studies concerned with the effect of strain have neglected finite size scaling. [13] Clearly it is necessary to consider both possible effects on an equal footing and it would be desirable to assign a particular amount of change in transition temperature to a particular cause. In this paper, we report a systematic study of the Curie temperature of a series of ferromagnetic LSCO films with different thickness on a variety of substrates.…”
mentioning
confidence: 99%